Contextual Theology and Biblical Teaching on Salvation: Reframing Soteriology through Digital Ecotheology - Sihombing, Altin (LP. Ma'arif Janggan Magetan, 2024)
The development of digital technology and the global ecological crisis demand a renewal of the theological way of thinking, especially in understanding the concept of salvation (soteriology). Contextual theology offers a relevant framework for reflection to reinterpret the Bible's teachings on salvation in digital and ecological contexts. This research aims to reconstruct the understanding of soteriology through the Digital Ecotheology approach that integrates theology, ecology, and technology in an interdisciplinary manner. The method used is Systematic Literature Review (SLR) by examining publications from the Scopus, Web of Science, Google Scholar, and Sinta databases over the past two decades. The results of the study show that there is a shift in the soteriological paradigm from the individualistic dimension to the cosmic, ecological, and digital dimensions. Salvation is understood as a relational restoration between God, man, creation, and technology, which is realized through ecological responsibility and digital ethics. This finding is that today's theology must be dialogical, contextual, and oriented towards the wholeness of creation. This research recommends the development of a systematic theology that combines ecological spirituality and digital awareness as the foundation of the 21st century faith proxy. Further studies are suggested to explore the application of Digital Ecotheological Soteriology in theological education, liturgy, and global church missions.